Penerapan Model Pembelajaran Cooperative Script terhadap Kemampuan Menelaah Struktur Teks Ulasan Cerpen pada Siswa Kelas VIII SMP Negeri 6 Lubuklinggau - Lestari, Susi; Abid, Syaiful (Ruang Publikasi Ilmiah, 2025)
The lack of students' understanding of the learning material on short story review texts in the Indonesian language subject, as seen from the test scores and interviews with Indonesian language teachers at SMPN 6 Lubuklinggau, prompted the researcher to conduct a study titled The Application of the Cooperative Script Model to the Ability to Analyze the Structure of Short Story Review Texts for Seventh Grade Students at SMPN 6 Lubuklinggau. The purpose of this study is to determine the significant improvement in the ability to analyze the structure of short story review texts among eighth-grade students at SMPN 6 Lubuklinggau. This study employed a quasi-experimental method without a comparison class. The population of the study consisted of all eighth-grade students at SMPN 6 Lubuklinggau, totaling 74 students. The research sample was selected using simple random sampling, resulting in class VIII.3 with 25 students being chosen. Data collection techniques included tests and non-test methods. The study results showed that the hypothesis was proven true, indicating that the Cooperative Script learning model was significantly effective in improving the ability to analyze the structure of short story review texts among eighth-grade students at SMPN 6 Lubuklinggau. This was evidenced by the results of the study using a